THE COMMITMENT OF PIMPINAN DAERAH ‘AISYIYAH MEDAN IN IMPLEMENTING LEGAL ASSISTANCE FOUNDING - Fajaruddin Fajaruddin; Rasta Kurniawati Br Pinem (Proceeding International Seminar of Islamic Studies, 2021)
There are so many cases related to women's rights that have not been touched by law with no assistance, for example; cases of violence against women, sexual harassment, pornography, porno-action which in this case involve the public. Then also in the form of private (civil) marriages, inheritance, parenting rights, neglect of women's rights in divorce, iddah, mut'ah, marital properties, rights of living, custody, including civil rights related to birth certificates that are still has a legal vacuum. There has been an increasing in divorce cases by 2,000 cases in 2018 and 2019. In 2020 this even increased from the previous two years, divorce cases until the end of August 2020, had reached 1,934 cases. This is certainly will increase until the end of December 2020. It shows that the rights and protection of women in the household have not been fulfilled. Aisyiyah needs to increase the role in this legal assistance.The methodology used to determine the commitment of the Pimpinan Daerah Aisyiyah Medan in providing legal assistance and guidance for women by distributing questionnaires to all branches of Aisyiyahin Medan. The respondent’s answers to the questions listed in the questionnaire were processed into data and analyzed and then concluded in this paper.The results of the questionnaire indicated that guidance in the field of law for women in Medan was continuously carried out. The implementation of the mentoring and coaching is scheduled to be carried out in the recitation of all branches of 'Aisyiyahin Medan. However, based on the observations, there is needed for evaluation in terms of several material aspects and their implementation. These commitments willcontinuously in the form of litigation and non-litigation, also conducting socialization of laws and legal counseling related to protecting women's rights. Totally there are 30 branches of 'Aisyiyah in Medan who were coordinated under the Law and Human Rights Council provided socialization and legal counseling which was carried out in rotation at the recitation of the'Aisyiyah.Keywords: Commitment, 'Aisyiyah, Coaching, Legal Assistance